A new species of Micragasma J. Sahlberg, 1900 (Coleoptera: Hydraenidae) from Crete. Issue 4 (2nd October 2017) - Hernando, Carles; Villastrigo, Adrián; Ribera, Ignacio
ABSTRACT: We describe a new species of Micragasma J. Sahlberg, 1900 (Coleoptera, Hydraenidae), which is here treated as a subgenus of Ochthebius Leach, 1815 . The new species, O . ( Micragasma ) minoicus sp. n., was found at the margins of a coastal rockpool in the island of Crete. The species differs from the other two known species of Micragasma in both external and genital characters, but shares with them the presence of small setiferous tubercles on the surface of the head, pronotum and elytra, and a strong medial gibbosity on the head. In some characters, such as the structure and shape of the aedeagus, O . ( M.) minoicus sp. n. is similar to other species of the genus Ochthebius, in particular of the subgenus Cobalius Rey, 1886, typical of coastal rockpools. http://zoobank.org/urn:lsid:zoobank.org:act:BCEAE1EE-7C5E-4017-A753-559738221502